2015
DOI: 10.1016/j.fss.2014.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Linguistic composition based modelling by fuzzy networks with modular rule bases

Abstract: This paper proposes a linguistic composition based modelling approach by networked fuzzy systems that are known as fuzzy networks. The nodes in these networks are modules of fuzzy rule bases and the connections between these modules are the outputs from some rule bases that are fed as inputs to other rule bases. The proposed approach represents a fuzzy network as an equivalent fuzzy system by linguistic composition of the network nodes. In comparison to the known multiple rule base approaches, this networked r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Next, using Eq. (7) for and , the distance between E1 according to DM1 and the FPIS is calculated as:…”
Section: Simulation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, using Eq. (7) for and , the distance between E1 according to DM1 and the FPIS is calculated as:…”
Section: Simulation Resultsmentioning
confidence: 99%
“…The following Table 1 and Table 2 are used by decision makers to evaluate the rating of alternatives and the importance of criteria, and Table 3 is used to determine the alternative level as the output, in generating fuzzy rule bases. (1, 3, 3, 5) Fair (F) 4 (3, 5, 5, 7) Medium Good (MG) 5 (5,7,7,9) Good (G) 6 (7, 9, 9, 10) Very Good (VG) 7 (9, 10, 10, 10) The following are the procedures involved in implementing a fuzzy network with merging rule bases to TOPSIS, based on Type 1-fuzzy set. Steps 1-6 are adopted from [16] and [12], while steps 7-10 are introduced as part of the proposed method in this paper.…”
Section: A Type-1 Fuzzy Set Implementationmentioning
confidence: 99%
“…The linguistic composition approach is applied to a case study on the first stage of an ore flotation process by using available data from the mining industry. This application is similar to the one described in [41] in that it uses the same approach but the case study here is quite The initial part of the rule base for the SFS is shown in Table 1. This rule base is derived from data about the product pricing process and in accordance with Equation (43).…”
Section: Simulation Resultsmentioning
confidence: 99%
“…This example considers an operand node N with output y and input x that is augmented with an input x AI . This node can be described by the Boolean matrix in Equation (33). In this context, node N represents a one-node FN that can be described by the block-scheme in Figure 8 and the topological expression in Equation (34).…”
Section: Examplementioning
confidence: 99%
“…In this respect, uncertainty is an obstacle to accuracy as it is harder to build an accurate model from uncertain data [29][30][31][32][33][34]. Furthermore, dimensionality represents an obstacle to efficiency because it is more difficult to reduce the amount of computations in a FID sequence for a large number of rules [35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%